You are unstoppable! : how to understand your feelings about climate change and take positive action together - Kenny-Woodard, Megan; Kennedy-Williams, Patrick; George, Jordanna (London; Philadelphia : Jessica Kingsley Publishers, 2023)
"It's normal to feel strong emotions like fear, anger or sadness about climate change. This book helps you learn how these emotions may affect you and your behaviour and shows how to transform your worries into positive climate action. With simple tips and tricks, you can ease your climate anxiety and help the planet too"--
Includes bibliographical references.
Keywords: Environmental psychology -- Juvenile literature; Climate changes -- Juveline literature -- Psychological aspects; Environmentalism -- Juveline literature